Application of optimization algorithms for robot systems designing. (20th January 2018) - Sapietová, Alžbeta; Sága, Milan; Kuric, Ivan; Václav, Štefan
The article presents the design and application of multi-software platform for solving kinematic synthesis of robot manipulator systems. It also presents a modern theoretical and application approach for modelling coupled mechanical systems, which include mobile robots. Due to high requirements for accuracy, efficiency, reliability and life cycle of technical equipment, several parameters ensuring optimal operating parameters need to be taken into account while dealing with the design. This is the reason for linking computational models to optimization algorithms that allows us to find the appropriate design parameters of analysed mechanical system, mechanisms, including mobile robots mostly by iterative way. The commercial working interface of the program ADAMS and open architecture of MATLAB programming language enable to share common data while dealing with model simulations in parallel. Both of them were used while designing and implementing the algorithm for the evaluation and optimization of parameters of technical equipment from the point of view of selected properties. While working on the task of the spatial mechanism of the six-member robot manipulator system, the algorithm solving the optimal parameters was created by applying the selected optimization techniques of the program MATLAB. Presented algorithm involves the creation of a map operating positions, which is further linked to the solution of the motion of interest points in the robotic system following a prescribed trajectory. This requires the geometry optimization of the selected members of the spatial robotic system in order to achieve such parameters so that the trajectory of the interest point of the output member would precisely match with the prescribed trajectory. It is important to note that these types of tasks create wider space for solving the assignments dealing with the development and application of technical equipment like mobile robots and their outputs that are linked to the needs of the practice.